Assessment of pulmonary outcomes, exercise capacity, and longitudinal changes in lung function in pediatric survivors of high‐risk neuroblastoma. Issue 11 (12th August 2019) - Stone, Anne; Friedman, Danielle Novetsky; Kushner, Brian H.; Wolden, Suzanne; Modak, Shakeel; LaQuaglia, Michael P.; Costello, Jessica; Wu, Xian; Cheung, Nai‐Kong; Sklar, Charles A.
Abstract: Background/objectives: Survivors of high‐risk neuroblastoma (NB) are exposed to multimodality therapies early in life and confront late therapy‐related toxicities. This study assessed respiratory symptoms, exercise capacity, and longitudinal changes in pulmonary function tests (PFTs) among survivors. Design/methods: Survivors of high‐risk NB followed in the long‐term follow‐up clinic at Memorial Sloan Kettering Cancer Center were enrolled. Symptom and physical activity questionnaires were completed. Medical records were reviewed for treatments and comorbidities. Participants completed spirometry, plethysmography, diffusion capacity of the lung for carbon monoxide, 6‐minute walk tests (6MWTs), and cardiopulmonary exercise testing. Questionnaires and PFTs were repeated at least one year after enrollment. Results: Sixty‐two survivors participated (median age at study: 10.92 years; median age at diagnosis: 2.75 years; median time since completion of therapy: 5.29 years). Thirty‐two percent had chronic respiratory symptoms. Seventy‐seven percent had PFT abnormalities, mostly mild to moderate severity. Thirty‐three completed 6MWTs (median, 634.3 meters); eight completed cardiopulmonary exercise tests (mean VO2 max: 63% predicted); 23 completed a second PFT revealing declines over a median 2.97 years (mean percent predicted forced vital capacity: 79.9 to 70.0; mean forced expiratory volume in 1 second: 81.6 to 69.9). Risks for abnormalities included thoracic surgery, chest radiation therapy (RT), thoracic surgery plus chest RT, and hematopoietic stem cell transplant. Conclusions: In this cohort of survivors of high‐risk NB, PFT abnormalities were common but mostly mild or moderate. Maximal exercise capacity may be affected by respiratory limitations and declines in lung function may occur over time. Continued pulmonary surveillance of this at‐risk population is warranted.